Assessment of neurological symptoms in adult hydrocephalus occlusus. A pilot study. (August 2021) - Wolfsegger, Thomas; Assar, Hamid
Highlights: The triad of gait disturbance, incontinence, and dementia in idiopathic normal pressure hydrocephalus (iNPH) can also be observed in hydrocephalus occlusus (HO). There is no similar scale in HO research to assess neurological symptoms. Clinical signs of HO are analyzed with the new iNPH Scale. The presented iNPH Scale evaluates neurological symptoms and surgical outcome in HO. Abstract: Background: Comprehensively describe and compare (pre⁄postoperatively) the clinical symptomatology in adult non-communicated hydrocephalus. Associated hydrocephalus signs were analyzed with the idiopathic Normal Pressure Hydrocephalus Scale (iNPH Scale). A standardized clinical scale for non-communicated hydrocephalus is currently not in use. Methods: Ten patients with hydrocephalus occlusus (HO) were analyzed. Hydrocephalus signs were examined with the iNPH Scale in gait, neuropsychology, continence, and balance before and three months after treatment with shunt operation or third endoscopic ventriculostomy. Results: Patients significantly improved in iNPH total score (25.8%) and gait score (35.4%) three months after neurosurgical intervention. Domain scores in neuropsychology, continence, and balance reached statistical trends (p ≤ 0.066). Most clinical symptoms and signs at baseline improved after surgery (dizziness, lapse of concentration, gait instability, and headache). Conclusion: Patients with non-communicated HO also showed classical hydrocephalus symptoms as communicated in iNPH patients. The iNPH Scale allows a structured neurological assessment over the disease's progress and surgical intervention. Further studies with a larger patient samples are necessary to support our results.